Vitrectomy in diabetic macular edema - Nowosielska, Agnieszka; Robaszkiewicz, Jacek; Graczyńska, Ewa; Czarnecki, Wojciech; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Macular edema remains one of the important therapeutic issues. Vitero-macular tractions are said, to be the cause of persistent, non responding to laser treatment diabetic macular edema. Surgical removal of these tractions is used in treatment of non resolving macular edema. However, vitrectomy in treatment of diabetic macular edema remains the experimental, method requiring further studying.